Determinan Pajak Penghasilan Badan Pada Perusahaan Sektor Industri Barang Dan Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020 - Muhammad Akbar Fauzi; Susanti Usman (Owner : Riset dan Jurnal Akuntansi, 2023)
Manufacturing companies are businesses that convert raw materials into finished or semi-finished products. Both human and mechanical power are used to manage these basic materials. This study aims to determine the determinants of operating expenses, liquidity, leverage, and profitability for the years 2016 to 2020 on corporate income tax on companies in the consumer goods and industrial sector listed on the Indonesia Stock Exchange. The website www.idx.com and the connected company website are used as secondary data sources and quantitative data types in this research technique. Purposive sampling was used to select the sample, which consisted of 25 companies from the consumer goods and industrial sectors that had been listed on the Indonesia Stock Exchange for at least five years. SPSS version 26 was used to process multiple linear regression, the analytical technique used in this study. The results of this study are only operating costs and profitability that have a significant impact on corporate income tax, while liquidity and leverage have no effect. The effect of operating expenses, liquidity, leverage, and profitability on corporate income tax occurs simultaneously.